Analysis and Comparison of Server Migration Performance on Amazon Web Services and Google Cloud Platform - Yovanka, Diva Nuranty; Suranegara, Galura Muhammad; Setyowati, Endah (Journal La Multiapp, 2024)
Cloud computing has emerged as a technology increasingly embraced by numerous enterprises to operate servers with high availability. The multi-cloud strategy is increasingly employed to manage servers across various platforms, guaranteeing service continuity despite disruptions on any single platform. This study analyzes and compares the migration performance of Amazon Web Services (AWS) and Google Cloud Platform (GCP) across two scenarios: migration in a homogeneous environment and migration in a heterogeneous environment, utilizing the metrics of migration time and downtime. According to the research findings, in homogenous environment migration, GCP excelled in both migration duration and downtime. In heterogeneous environment migration, AWS demonstrated superior migration speed.